Reliability and Validity Testing of the Assessment of the Environment for Person-Centered Management of BPSD and Assessment of Policies for Person-Centered Management of BPSD Measures. Issue 3 (2nd July 2020) - Resnick, Barbara; Kolanowski, Ann; Van Haitsma, Kimberly; Galik, Elizabeth; Boltz, Marie; Zhu, Shijun; Ellis, Jeanette; Behrens, Liza; Eshraghi, Karen; Viviano, Nicole; Jao, Ying-Ling
Abstract: The purpose of this study was to test the reliability and validity of the Assessment of the Environment for Person-Centered Management of BPSD and the Assessment of Policies for Person-Centered Management of BPSD. The sample included 35 long term care facilities. There was evidence of reliability based on internal consistency and test-retest reliability of both measures. There was some evidence of validity based on Rasch model testing and INFIT and OUTFIT statistics. Across both measures, there were six items that were endorsed as present by all facilities. The INFIT and OUTFIT statistics were all within the expected range of .5 to 1.5 with the exception of four high OUTFIT statistics for the Assessment of the Environment for Person-Centered Management of BPSD. For the Assessment of Policies for Person-Centered Management of BPSD, there were two items that had high INFIT statistics and six with low OUTFIT statistics and one with high OUTFIT statistics. Measure revisions are suggested including removal of some poor fitting items, items with no variance, and adding items to differentiate those very high in evidence of environments and policies that manage BPSD.